(untitled)
Let \(V\) be a ternary ring of operator, and let \(B\) be a \(C^*\)-algebra. We study the structure of the ideal space of the operator space injective tensor product \(V ^tmin B\) via two maps: align* Φ(I, J) = (q_I ^tmin q_J) and Δ(I, J) = I ^tmin B + V ^tmin J. align* We prove that \(Φ\) is continuous with respect to the hull-kernel topology, and that its restriction to primitive and prime ideals defines a homeomorphism onto dense subsets of the respective ideal spaces of \(V ^tmin B\). We prove that if \(Φ = Δ\), then \(Φ\) induces a homeomorphism between the space of minimal primal ideals of \(V ^tmin B\) and the product of the spaces of minimal primal ideals of \(V \) and \(B\). , number=3, journal=Journal of Informatics and Mathematical Sciences, year=2025, month=Sep., pages=267–276